Implementation Of Village Fund Allocation (ADD) In Rhieng Krueng Village, Meureudu District, Pidie Jaya District - Italina, Cut; Jamil, M. (LPPM Universitas PGRI Sumatera Barat, 2024)
The implementation of the village revenue and expenditure budget is used in accordance with predetermined regulations where the implementation is guided by the regulation of the Minister of Home Affairs Number 20 of 2018 concerning Village Fund Management as well as in the management of village funds which is carried out in accordance with what has been stipulated in Permendagri 113 of 2014 concerning Village Fund Management in fact the implementation and management of village funds in Gampong Rhieng Krueng has not fully run as these two regulations, this study uses a qualitative approach with a descriptive writing method with a research focus on the management of village funds through the dimensions of planning, implementation, administration and accountability while the implementation of village funds the focus of research is carried out through village income, village expenditure and village costs. From the results of the research conducted that the village revenue carried out by Gampong Rhieng Krueng is still not maximized, especially in the original income of Gampong and increasing self-help and community participation, village expenditures carried out in the absence of budget inclusion in disaster management and emergencies, village costs carried out on expenses that have not been maximized. Against the management of Gampong Rhieng Krueng funds that the planning dimension is still not optimal in determining the priority scale of development, the implementation dimension in the preparation of DPA and RAB is still carried out by other parties not the Gampong apparatus, the administration dimension made by the Gampong treasurer is not optimal, especially in filling in each series of activities that result in money out is still weak, and the accountability dimension has also not been done well in accountability to the government which is not on time and to the community is done once a year. The conclusion is that the implementation and management of the Gampong Rhieng Krueng fund carried out by the Gampong government has not been maximized as expected.